Primordial Black Holes And How Strings Get Created Into Matter In The Early Universe - McGraw Jr., David (JOURNAL OF ADVANCES IN PHYSICS, 2024)
The C-Neutralino is the major particle that drives the beginning of our universe. It decays into other particles including protons and electrons. Primordial Black Holes are also important in the development of our universe. They connect astrophysical constraints on sources of cosmic rays. Primordial Black Holes play a role in element abundance and the spectrum of the CMB. They are particle and matter creators. Primordial Black Holes can be a source of any species of particles in our space-time. In the end, they can shed new light on problems in Cosmology. Primordial Black Holes are the solution to inhomogeneous primordial structures in the early universe. C-Neutralinos are the particle that contributes to creation and also contribute to dark matter in our universe. It is the major source of dark matter in our universe. In the early universe, the cosmological principle did not exist. The inhomogeneous universe we see today evolved after about 1 billion years after the creation of our universe.